STUDENT CAREER PLANNING REVIEWED FROM BENGKULU SUBCULTURE - Juwanto, Juwanto; Nurihsan, Juntika; Maya, Dian Mustika (Universitas Pendidikan Indonesia, 2024)
Vocational High Schools (SMK) as one of the Vocational education institutions are required to prepare graduates who are ready to work according to their areas of expertise so that good career planning maturity is needed. This survey was conducted to find out the extent of readiness in the career planning of SMK students in terms of the Bengkulu Subculture. Respondents who were taken were class X State Vocational School students through distributing questionnaires. Data analysis used a quantitative descriptive analysis technique, namely the analysis of data that has been given a score with a statistical measurement scale. The survey results show that vocational students' career planning is still in the low category. The low level of career planning occurs in 6 tribes in Bengkulu, namely the Lembak Tribe, Rejang Tribe, Serawai Tribe, Muko-Muko Tribe, Kaur Tribe and Pekal Tribe. Student career planning in each tribe in Bengkulu on the indicator of studying career information has a score of 72.11%, understanding self-potential with a score of 70.28%, participating in training activities that support career choices with a score of 69.59%, discussing with other people 70.49% and participating in extracurricular activities with a score 69.62%.